THE EFFECT OF RISK TAKING ON PRODUCT ADVANTAGE WITH INNOVATIVE AND PROACTIVE AS MODERATING VARIABLES IN CULINARY MSME IN TANGERANG - Rodhiah Rodhiah; Nur Hidayah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aimed to examine the effect of risk taking on product advantages with innovative and proactive as a moderating variable on MSMEs in Tangerang. Total of 90-100 MSMEs were studied by taking samples. The sampling technique used was convenience sampling based on the ease and willingness of MSMEs when collecting data. The technique of collecting data was done by distributing questionnaires to respondents who were selected as sample members. The data obtained will be analyzed by SEM using Partial Least Square (PLS). The results showed that there was no effect of risk taking on product advantages with innovative and proactive as a moderating variable in MSMEs. However, there is an effect between being proactive on product advantages. Keywords: Risk Taking, Product Advantages, Innovative, Proactive, MSME